2016
DOI: 10.1111/ans.13517
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of kidney paired donation transplants involving multiple donor and recipient surgeons across Australia

Abstract: The study provided a favourable audit of kidney transplant activity, despite challenges of simultaneous surgery, organ transport coordination and prolonged CIT. The decision to ship donor kidneys rather than the donor was demonstrated to be feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Evidence from the United States, Australia, the United Kingdom, and Europe has demonstrated that shipping kidneys is safe with CITs of up to 16 h. However, this increases the risk of DGF, which may reduce graft and patient survival and increase incidences of acute rejection. 12,34-37…”
Section: Kidney Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the United States, Australia, the United Kingdom, and Europe has demonstrated that shipping kidneys is safe with CITs of up to 16 h. However, this increases the risk of DGF, which may reduce graft and patient survival and increase incidences of acute rejection. 12,34-37…”
Section: Kidney Donorsmentioning
confidence: 99%
“…Evidence from the United States, Australia, the United Kingdom, and Europe has demonstrated that shipping kidneys is safe with CITs of up to 16 h. However, this increases the risk of DGF, which may reduce graft and patient survival and increase incidences of acute rejection. 12,[34][35][36][37] Deceased Donor Kidney Transplantation Rates of DGF in deceased donor kidney transplantation range from 10% in standard donation after brain death (DBD) kidneys to 93% in uDCD 4,7,8,10,[16][17][18][19][20][21][22][23]27,38 (Table 1). The outcomes of graft and patient survival at 1 y are good but slightly lower in comparison to living donor kidneys.…”
Section: Kidney Donors Live Donor Kidney Transplantationmentioning
confidence: 99%
“…DN is the leading cause of end-stage renal disease (ESRD) (Toth-Manikowski and Atta, 2015). Currently renal transplantation is the treatment of choice for patients with ESRD due to improvements in graft survival; however, the wait for an available organ may extend to 3-5 years (Allen et al, 2018;Clayton et al, 2018). Dialysis is clearly not the answer, at least as it is currently employed, as the 5-year survival rate for patients receiving some form of hemodialysis hovers only at around 20-40% (Huff, 2020).…”
mentioning
confidence: 99%